2000
DOI: 10.1063/1.126894
|View full text |Cite
|
Sign up to set email alerts
|

Energy dependence of transient enhanced diffusion and defect kinetics

Abstract: Boron, a p-type dopant, experiences transient enhanced diffusion (TED) via interstitials. The boron TED and {311} dissolution rates are explored as a function of implant energy dependence. Silicon implants of 1014/cm2 at various energies were used to damage the surface of a wafer with an epitaxially grown boron marker layer. Samples were annealed at 750 °C for 15–135 min to observe the diffusion exhibited by the marker layer and to correlate this with the dissolution of {311} type defects. The diffusion enhanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2001
2001
2007
2007

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 6 publications
1
6
0
Order By: Relevance
“…As stated in [1], the calibration of the model for small interstitial clusters and {311} defects is based on the interstitial supersaturation evolution data extracted from boron marker layers experiments [10,11] and on the data of interstitial concentration in {311} defects as well as {311} density extracted from TEM measurements [12][13][14][15][16]. For experiments with relatively low interstitial dose and small thermal budget, no dislocation loops can nucleate.…”
Section: Resultsmentioning
confidence: 99%
“…As stated in [1], the calibration of the model for small interstitial clusters and {311} defects is based on the interstitial supersaturation evolution data extracted from boron marker layers experiments [10,11] and on the data of interstitial concentration in {311} defects as well as {311} density extracted from TEM measurements [12][13][14][15][16]. For experiments with relatively low interstitial dose and small thermal budget, no dislocation loops can nucleate.…”
Section: Resultsmentioning
confidence: 99%
“…This may be expected due to the projected range ͑100 Å͒ being furthest from the interface. [12][13][14] The presence of a higher supersaturation of excess interstitials may be the reason fewer extended defects are observed. 4.…”
Section: Discussionmentioning
confidence: 99%
“…Saleh et al 13 varied the distance to the surface, with implantation energies from 20 to 160 keV, and measured the characteristic time constants for TED ͑by measuring the junction depth broadening of a boron marker layer and assuming an exponential decay in diffusivity with time͒ and ͕113͖ defect dissolution ͑measured from the slope of the fast decay region of the Si interstitial dose in ͕113͖ defects versus time͒. They observed that while the characteristic time for TED clearly increases with the implanted energy-distance to the surface, the characteristic time for ͕113͖ defect dissolution varies very weakly with the implanted energy.…”
Section: A Spatial and Temporal Evolution Of A Layer Ofˆ113‰ Defectsmentioning
confidence: 98%
“…They showed that the ͕113͖ defects dissolve uniformly across the layer, and the width of the layer does not change until the ͕113͖ defects nearly completely dissolve. Saleh et al 13 claimed no correlation between TED and ͕113͖ dissolution since TED depends strongly on implant energy but the ͕113͖ dissolution is weakly dependent.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation